The moderating role of self-compassion on the relationship between emotion-focused impulsivity and dietary restraint in a diverse undergraduate sample. (August 2022) - Breiner, Courtney E.; Scharmer, Christina; Zon, Caitlyn; Anderson, Drew
Abstract: Objective: High levels of emotion-focused impulsivity (e.g., negative urgency) are significantly related to disordered eating behaviors, including dietary restraint. The objective of the current study was to understand the moderating role of self-compassion between emotion-focused impulsivity and dietary restraint in a diverse undergraduate sample. We hypothesized that high levels of self-compassion would protect individuals with high levels of emotion-focused impulsivity from engaging in high levels of dietary restraint. Method: Participants ( n  = 607, M age   =  18.8, 63 % female, 45.3 % White) completed the UPPS-P, Eating Disorder Examination Questionnaire, and the Self-Compassion Questionnaire as part of a larger study examining eating behaviors in college students. Results: Negative urgency, but not positive urgency, was related to dietary restraint. Self-compassion moderated the relationship between both forms of impulsivity and dietary restraint, such that individuals with high emotion-focused impulsivity and high self-compassion had lower dietary restraint than individuals who had high emotion-focused impulsivity and low self-compassion. Discussion: Emotion-focused urgency is a risk factor for dietary restraint; both factors are highly correlated with more severe eating pathology, such as binging and purging behaviors. Self-compassion may buffer against the risk of emotion-focused impulsivity on engaging in dietary restraint behaviors in a community sample, which may inform our understanding of preventative interventions against eating pathology. These results should be replicated in clinical populations and across eating disorder diagnoses. Highlights: Dietary restraint is a key mechanism underlying all eating pathology. Negative but not positive urgency is positively related to dietary restraint. Self-compassion moderates the relationship impulsivity and dietary restraint.